Realising a Clean Denpasar: Waste Management Based on Good Governance and the Principles of Tri Hita Karana - Agus Surya Manika; Ni Nengah Agustin Citrawati (LEGAL BRIEF, 2026)
Waste is a complex problem in Denpasar City, and the Denpasar City Government has introduced various regulatory measures to address this issue, including Denpasar Mayoral Regulation Number 15 of 2023 concerning Culture-Based Waste Management. Despite the existence of this regulation, a significant gap remains between the waste management policies established by the local government and their implementation by communities at the local level. Community participation in waste sorting, reduction, and environmentally responsible disposal practices has not yet been fully aligned with the objectives of the regulation, indicating that the policy has not been implemented effectively in practice. This gap demonstrates that the integration of good governance principles and the local wisdom values of Tri Hita Karana has not yet been optimally translated into community behavior and institutional practices. This article examines waste management in Denpasar City from the perspective of good governance and the implementation of Tri Hita Karana values. This study employs normative legal research to analyze the normative gap within Denpasar Mayoral Regulation Number 15 of 2023, particularly the absence of clear legal provisions that strengthen the implementation of good governance principles and Tri Hita Karana values to bridge the gap between policy and community practices. The research applies statutory, conceptual, and case approaches. The findings reveal that the principal obstacle to effective waste management is not merely limited community awareness but the absence of explicit legal provisions governing community participation, institutional coordination, accountability, and supervision within the existing regulatory framework. The study further finds that the values of Parahyangan, Pawongan, and Palemahan can function as legal-cultural principles that strengthen environmental governance by fostering moral responsibility, collective participation, and environmental stewardship. The novelty of this research lies in the development of a normative legal framework that integrates enforceable good governance principles with the culturally embedded values of Tri Hita Karana to bridge the gap between regulatory policy and community practice. This integrated framework provides a legal basis for improving regulatory implementation and offers a model for sustainable, participatory, and culturally responsive waste governance in Indonesia